Comparative Analysis of Similarities and Differences between Null Hypotheses, Assumption of Breach (Indian Journal of Advanced Mathematics (IJAM), 2024)
The main purpose of this paper is to comparatively study the similarities and differences between of the , null hypothesis and assumption of breach .The null hypothesis , in applied researches, particularly experiments for confirm or rejection .a hypothesis, regard to inferential statistics That used in many different fields of humanities researchers, particularly psychology, education, management and sociological placed assumption of breach, to prove geometric proposition( theorems), which hypothetical temporary, that with the help of reasoning, the false statements, it we conclude. Such a statement may deny our hypotheses or assume reduction ad absurdum. The use of these two words separately and hypothesis alternative in abundance, the world of science and research, has been discussed, but the relationship between these words, mention, yet. Isn’t .This article describes the relation of these assumptions. Likewise, in writing, to the similarity, their differentiation, are mentioned. Including the results, that is, the achieve results null hypothesis, researcher with the error is encountered, but In the Reduction ad absurdum the achieve results, not an error.